ESTRATEGIA DE BRANDING PARA GENERAR POSICIONAMIENTO DE LA EMPRESA “SARATEX” EN LA CIUDAD DE RIOBAMBA. - Díaz Ruilova, Valeria Katherine (2019)
Nowadays there are many techniques and mechanisms to announce the products or services of a company, as in the case of advertising, public relations and marketing, which are adapted to the situation of each company due the world has been evolving in the field of brand communication. In the present project, a branding strategy was developed to generate the positioning of the Saratex company in the city of Riobamba. It is remarkable the grown that the company has had in the city and thanks to this has allowed marketing its sportswear in several cities and cantons of the country. Due to the economic crisis that the country croses, the Saratex company has a shortage in its sales by major and minor, so it is necessary to créate a brand for its clients identify it, and the same way it can be positioned in the market local and national, allowing conquer new customers. Therefore, from his study, we can conclude that through Robert Scott`s methodology, the four phases were executed, in order to develop the brand strategy for the Saratex company in the city of Riobamba, in which it is posible to demonstrate the creation of the brand, the brand manual and the strategies of brand that will help to position the company.